(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2013)
Summary Multiple myeloma, generally a disease of the elderly, is a complex disorder that causes a multitude of clinical symptoms and signs and therefore presents significant diagnostic challenge to the clinician specially if the age of onset is unusually early. Here we present one young patient suffering from multiple myeloma. JCMCTA 2013; 24 (1):67-69